Storage Proteins Are Driving Pediatric Hazelnut Allergy in a Lipid Transfer Protein-Rich Area - Teresa Valbuena; Marta Reche; Guadalupe Marco; Inmaculada Toboso; Anna Ringauf; Israel J. Thuissard-Vasallo; Daniel Lozano-Ojalvo; Mónica Martínez-Blanco; Elena Molina (Foods, 2021)
Oral food challenge (OFC) remains the gold standard for the diagnosis of food allergies. However, this test is not without risks, given that severe allergic reactions can be triggered while it is conducted. The purpose of this study is to identify potential demographic variables, clinical characteristics of the patients and biomarkers that may be associated with severe reactions during the hazelnut oral challenge test. The sample included 22 children allergic to hazelnut who underwent a tree nut skin prick test (SPT), specific IgE (sIgE) to hazelnut, component-resolved diagnosis (CRD) with different hazelnut allergens (Cor a 1, Cor a 8, Cor a 9, Cor a 11, Cor a 14), and a single-blind placebo-controlled challenge with hazelnut. A statistically significant relationship was found between the severity of the reaction and the highest values of sIgE to hazelnut, Cor a 11 and Cor a 14, cumulative symptom-triggering dose and sunflower seed sensitization. The use of the CRD is a useful tool to identify patients at higher risk of developing a severe reaction. In this pediatric population sample from Spain, storage proteins were confirmed to be most involved in hazelnut allergy and the development of severe reactions.